Young and Older Adults May Utilize Different Cognitive Abilities When Performing a Spatial Recognition Memory Test With Varying Levels of Similarity. (January 2020) - DeFord, Nicole E.; DeJesus, Shannon Y.; Holden, Heather M.; Graves, Lisa V.; Lopez, Francesca V.; Gilbert, Paul E.
We used signal detection theory to evaluate spatial recognition memory utilizing a behavioral test hypothesized to tax pattern separation. Correlations with standardized neuropsychological tests also were examined. Healthy young ( n = 40) and older ( n = 30) adults completed a spatial recognition memory test involving high- and low-similarity conditions. Using d' as the dependent variable, we found that older adults were significantly impaired relative to young adults on the high- and low-similarity conditions ( p s < .05). Both groups performed significantly better in the low-similarity condition compared to the high-similarity condition ( p < .05), with young adults exhibiting greater improvement relative to older adults. We also found that young adults may rely on spatial attention abilities when performing our test, while older adults might rely on memory and executive function abilities. These findings indicate that young and older adults may utilize different cognitive abilities when performing certain spatial memory tests.